Penerapan Metode Analytical Hierarchy Process (AHP) dalam Sistem Pendukung Keputusan Pemilihan Destinasi Wisata Danau di Provinsi Jambi - Eka Martyani; Ikke Yamalia; Rd. Rahmat Dauli (JOURNAL VISION TECHNOLOGY (V-TECH) ISSN : 2622-9315 (Online - Elektronik), 2022)
A tourist object is the embodiment of human creation, way of life, art and culture and the history of the nation and places of natural conditions that have an attraction to visit. Jambi province has many popular lakes that are still not exposed to the public, some of these lakes are the best places for tourists to enjoy water tourism. But here will be discussed only a few lake destinations. With a fairly large number of lake attractions, sometimes it makes tourists hesitate to choose a tourist attraction to visit when they go to Jambi Province. To overcome this problem In this decision support system, the Analytical Hierarchy Process (AHP) method is used to determine the best alternative from the lake tourist destination to be selected. Six basic criteria used are mileage, transportation, facilities, entrance fee, scenery, and security. The AHP method is used to calculate the weight of each criterion to produce the best alternative. This Decision Support System is expected to be able to provide assistance and recommendations for the best alternative to tourists in choosing tourist destinations that are in accordance with their wishes.